Novel Renewable Energy as Resources for Environmentally Friendly National Energy Security: The Existence and the Readiness of the Regulatory Framework - Aditya Prastian Supriyadi; Adelia Rachmaniar; Aris Mustriadhi; Hasyimi Pradana (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Carbon gas emissions that come from the use of non-renewable energy have a bad impact on the environment. So, comes the idea of ​​transforming Novel Renewable Energy as the main energy source because it is more environmentally friendly. This is a challenge for Indonesian. Because Indonesia has the potential for Novel Renewable Energy which can be utilized as the main source of national energy security. For the proposal to be successful, it must be accompanied by qualified regulations. However, the problem today that Indonesia does not have specific independent rules regulating Novel Renewable Energy. The purpose of this paper is to analyze the potentials of Indonesian’s Novel Renewable Energy as an alternative to the main source of national energy security. Besides, it is also to analyze legal support so that the environmentally friendly Novel Renewable Energy optimization program has the right legal basis. The research method in this paper uses normative research methods. The research approach of this paper uses a conceptual approach related to Novel Renewable Energy. The results show that Indonesia has big potential for Novel Renewable Energy as the main source of national energy security. So the environment-friendly Novel Renewable Energy will be realized as a source of national energy security.